Reingeniería de procesos en el área operacional de la empresa de catering el refugio de Belén ubicada en la ciudad de Ibarra - Vallejos Oña, Marco Sebastián (2022)
The reengineering of processes in the operational area of the catering company El Refugio de Belén, located in the city of Ibarra, is based on the premise of improving the procedures that are carried out in order to provide services to both internal and external clients. . That is why the present investigation is based on carrying out a theoretical foundation on previous research on the subject, at the international, national and also at the local level. Procedure that delves deeper into the conceptual framework, mainly regarding concepts related to the implicit variables of the investigation, both dependent and independent, at the same time that the design of the present investigation is considered to be non-experimental of a transversal type, due to that describes the incidences on the procedures of the catering company El Refugio de Belén, at a specific moment, without considering its evolution through time. An exploratory, descriptive and explanatory investigation is used to collect the information and develop the improvement proposal in the company, through observation, interview, survey and questionnaires, the corresponding information was collected to carry out the corresponding process reengineering.